Pengaruh Konsentrasi Pupuk Kalium Nitrat (KNO3) dan Kalium Dihidrophosphate (KH2PO4) Terhadap Pertumbuhan dan Hasil Cabai Merah Keriting - Gilang Apriliyas Pangestu; Erie Maulana; Fahri Ali; Raida Kartina; Betari Safitri; Dede Tiara (Politeknik Negeri Lampung, 2023)
Curly red chilies are one of the horticultural products that have the potential to be developed because they have high economic value, however the production of curly red chilies in Lampung Province has continued to decline in the last 4 years. One way to increase production value is to increase soil fertility by increasing fertilization. Fertilization is carried out to replace nutrients lost due to rainwater by using fertilizer containing the elements N, P and K, one of which is KNO3 and KH2PO4 fertilizer. The aim of this research is to find out which combination of KNO3 and KH2PO4 is better and to find out whether the single application of KNO3 and KH2PO4 is good for the growth and yield of curly red chili plants. The research used a factorial randomized block design consisting of 2 factors. The first factor is the concentration of KNO3 fertilizer, with 3 levels, namely 3; 4; 5g/l. The second factor is the concentration of KH2PO4 Fertilizer, with 3 levels of 3,5; 4,5; 5,5g/l. Each treatment was repeated 3 times, so there were 9 treatment combinations and 27 experimental units. The variables observed were plant height, stem diameter, number of shoots, fruit weight per plant, number of fruit per plant and root length. Potassium nitrate (KNO3) fertilizer treatment with a concentration of 5 g/l and potassium dihydrophosphate (KH2PO4) 5,5 g/l had a significant effect on plant growth in plant height. Providing potassium nitrate (KNO3) fertilizer with a concentration of 4 g/l and potassium dihydrophosphate (KH2PO4) 5,5 g/l had a significant effect on plant growth including the number of branches and stem diameter. Providing potassium nitrate (KNO3) fertilizer with a concentration of 4 g/l and potassium dihydrophosphate (KH2PO4) 4,5 g/l had a significant effect on plant yields including the number of fruit/plants and the weight of the fruit/plant.